The Impact of the COVID-19 Pandemic on the Functionality of International Surgical Volunteer Organizations - Lyons, Spencer; Xu, Amy L.; Durand, Wesley M.; Patel, Shyam; Oni, Julius K.; Babu, Jacob M. (Frontiers in Surgery, 2022)
Background: Surgical volunteer organizations have been severely limited during the ongoing coronavirus disease pandemic. Our purpose was to identify obstacles to surgical volunteer organizations secondary to COVID-19 and their responses. Methods: Forty-one surgical volunteer organizations participated in a web-based survey (156 invited, 26% response rate). Respondents were separated into two groups: low donations surgical volunteer organizations (≤ 50% donations of previous year; n=17) and high donations surgical volunteer organizations (≥75%; n=24). Univariate analyses were used to compare the two cohorts. Results Of responding surgical volunteer organizations, 34 (83%) were unable to maintain full functionality due to COVID-19; 27% of high donations versus 0% of low donations surgical volunteer organizations (p=0.02). The three leading obstacles were finances/donations (78%), fewer volunteers (38%), and inadequate personal protective equipment (30%). In response, 39% of surgical volunteer organizations developed novel E-volunteering opportunities. For support, 85% of surgical volunteer organizations suggested monetary donations, 78% promotion through social media platforms, and 54% donation of personal protective equipment. Conclusion: The majority of surgical volunteer organizations were unable to maintain full functionality due to stressors caused by COVID-19, including limitations on finances, volunteers, and personal protective equipment.